Carcinoma of the recto-vaginal septum. Comprehensive literature review. (18th May 2016) - Lopez, N.; Grabowski, J. P.; De Santiago, J.; Zapardiel, I.
Abstract : Carcinoma of the recto-vaginal septum is an extremely rare entity. We performed a MEDLINE-based search on recto-vaginal septum carcinoma, focussing on its management, in order to clarify which are the best treatment options for this disease. In addition an unpublished case report has been added to the review. 34 case reports were included in our review. Surgery and adjuvant chemoradiation therapy seem to be the most common treatment option. However, since primary surgical treatment leads to mutilation by removing a large portion of the vagina and the anal sphincter with a permanent terminal colostomy, primary platinum-based chemoradiation therapy could be considered. In case of extragastrointestinal stromal tumours primary surgical treatment seems to be the best option. Due to the rarity of this entity only limited data is available. Therefore further investigation is necessary.